2022
DOI: 10.3390/jcm11123542
|View full text |Cite
|
Sign up to set email alerts
|

LVAD as a Bridge to Remission from Advanced Heart Failure: Current Data and Opportunities for Improvement

Abstract: Left ventricular assist devices (LVADs) are an established treatment modality for advanced heart failure (HF). It has been shown that through volume and pressure unloading they can lead to significant functional and structural cardiac improvement, allowing LVAD support withdrawal in a subset of patients. In the first part of this review, we discuss the historical background, current evidence on the incidence and assessment of LVAD-mediated cardiac recovery, and out-comes including quality of life after LVAD su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 122 publications
(315 reference statements)
0
9
0
Order By: Relevance
“…Thus, there is a need to design studies with disease- and intervention-specific patient inclusion criteria, consistent medication protocols and monitoring protocols to determine true myocardial dimensions for recovery. Myocardial recovery should be an intensive field of study in the coming years [ 61 , 65 ]. This is evident from the tendency of now official organizations to recategorize these patients, for example, the American Heart Association (AHA), which created the HFimpEF classification for patients, studied as a separate group those who, after therapeutic interventions, improved their cardiac function ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a need to design studies with disease- and intervention-specific patient inclusion criteria, consistent medication protocols and monitoring protocols to determine true myocardial dimensions for recovery. Myocardial recovery should be an intensive field of study in the coming years [ 61 , 65 ]. This is evident from the tendency of now official organizations to recategorize these patients, for example, the American Heart Association (AHA), which created the HFimpEF classification for patients, studied as a separate group those who, after therapeutic interventions, improved their cardiac function ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, both prospective and retrospective, have demonstrated the association between the use of neurohormonal inhibitors and reverse remodeling in patients with LVADs [ 42 , 43 , 60 , 61 ]. An interesting retrospective analysis of 12,144 LVAD patients from the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) revealed that those receiving any neurohormonal inhibitor at 6 months had a better survival rate at 4 years compared with patients not receiving neurohormonal inhibitor (56.0% vs. 43.9%) [ 62 ].…”
Section: Medical Treatment and Cardiac Rehabilitationmentioning
confidence: 99%
“…Recent studies show that continuous flow LVADs can improve the survival of end-stage heart failure patients and have been in current clinical use as a destination therapy or as a bridge-to-transplant ( 1 3 ). However, the use of LVAD has been reported to cause aortic insufficiency (AI), as early as 6 months, requiring continuous hemodynamic monitoring of the aortic valve (AV) post implantation ( 1 , 3 ). The pathophysiology of this LVAD-associated AI is partly related to the impact of the LVAD, causing degenerative changes and remodeling of the AV ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The surgical repair of the AV in the context of LVAD-associated anatomical remodeling generally includes ring annuloplasty ( 8 ). However, reports show that AV regurgitation can develop even after AV repair within a few months of LVAD implantation with concomitant annuloplasty ( 3 , 8 , 9 ). Hence, concomitant AVR with ring annuloplasty during LVAD implantation has been adopted and reported with feasible outcomes ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The correct operation of the valves ensures an appropriate hemodynamic state of the human being and the correct perfusion of organs, as well as tissue microperfusion. The valves, however, can be destroyed for various reasons [ 1 ].…”
Section: Introductionmentioning
confidence: 99%